Prevalence of Dental Caries Among Physically Disable Students of Primary School in Lahore - Shahzad Waheed Qureshi, Muhammad Moed Haidar Naqvi, Amna Mehwish Ikram, Adeel Haidar, Rehana Kausar, Tayyaba Nayab Shahid, Amina Tariq (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: This study aimed to report the incidence of dental caries among deaf students of primary school in Lahore Method: This descriptive crossectional study was conducted at 2 private primary schools for deaf students in Lahore. Sample of the study was 150 students who were completely deaf. Data was collected by screening of oral health maintenance of students by two dentists. Chi Square test was used to explore the age wise difference in occurrence of dental caries among deaf students of primary school in Lahore Results: Overall incidence of dental caries is quite high among deaf students of primary school in Lahore (112(74.67%). Results of chi square test revealed no significant difference of incidence of dental caries in terms of age (X2=4.597, P=.204). Conclusion: In Lahore, incidence of dental caries among primary school deaf students is quite high which need to be address. Moreover, age has no significant effect on the incidence of dental caries among primary school deaf students. Keywords: Dental caries, Deaf students, Primary school, Oral health maintenance